FULFILLMENT OF WOMEN’S POLITICAL RIGHTS IN A DEMOCRACY GOVERNMENT - wulandari, Dwita; Suryaningsi, Suryaningsi (Unmul Civic Education Journal, 2022)
Citizen rights are an authority possessed by citizens to do something according to the laws and regulations. The type of research used in this study is qualitative, the data collection technique is triangulation, the data analysis carried out is inductive. Based on informants' statements in in-depth interviews, it was found that the embodiment of women's political rights in a democratic society has pros and cons. So that the fulfillment of women's political rights is still not fully achieved. From the explanation above, we can also see that we should not distinguish between genders because we are all equal before God. Women and Men are Equal before God. Everyone has the right and opportunity to enter the government. human rights are natural rights, basic human rights, absolute rights. Democracy is a choice of a political system where the power to govern comes from those who are governed, namely a government that actively involves all members of society in decisions taken by those who are authorized.